A screening program to test and treat for Helicobacter pylori infection: Cost-utility analysis by age, sex and ethnicity. Issue 1 (December 2017) - Teng, Andrea; Kvizhinadze, Giorgi; Nair, Nisha; McLeod, Melissa; Wilson, Nick; Blakely, Tony
Abstract Background The World Health Organization recommends all countries consider screening forH. pylori to prevent gastric cancer. We therefore aimed to estimate the cost-effectiveness of aH. pylori serology-based screening program in New Zealand, a country that includes population groups with relatively high gastric cancer rates. Methods A Markov model was developed using life-tables and morbidity data from a national burden of disease study. The modelled screening program reduced the incidence of non-cardia gastric cancer attributable toH. pylori, if infection was identified by serology screening, and for the population expected to be reached by the screening program. A health system perspective was taken and detailed individual-level costing data was used. Results For adults aged 25–69 years old, nation-wide screening forH. pylori was found to have an incremental cost of US$196 million (95% uncertainty interval [95% UI]: $182–$211 million) with health gains of 14, 200 QALYs (95% UI: 5, 100–26, 300). Cost per QALY gained was US$16, 500 ($7, 600–$38, 400) in the total population and 17% (6%-29%) of future gastric cancer cases could be averted with lifetime follow-up. A targeted screening program for Māori only (indigenous population), was more cost-effective at US$8, 000 ($3, 800–$18, 500) per QALY. Conclusions This modeling study found thatH. pylori screening was likely to be cost-effective in this high-income country, particularly for the indigenous population. While further research is needed to help clarify the precise benefits, costs and adverse effects of such screening programs, there seems a reasonable case for policy-makers to give pilot programs consideration, particularly for any population groups with relatively elevated rates of gastric cancer.